Game-Based Learning of the Structure and Functioning of Body Cells in a Foreign Language: Effects on Motivation, Cognitive Load, and Performance - Stiller, Klaus Dieter; Schworm, Silke (Frontiers in Education, 2019)
Research has evidenced that digital educational games can be effective tools to impart knowledge. Researchers have recommended to focus on motivation and gaming load and their interaction when investigating learning process and success. Gaming expertise and the English proficiency of learners seem to be further important aspects of learning success, especially when non-native speakers play an English game. However, knowledge about the motivational and cognitive impact of games and learner characteristics on learning outcomes needs to be augmented and clarified. The present study aimed to address this need. We conducted an experimental media comparison to investigate the effects of game play and expertise in gaming and English on motivation, cognitive load, and performance. The participating German university students were randomly assigned to an educational gaming group and a hypertext group. Aspects of motivation were assessed before and after studying and gaming, cognitive load was rated during and after learning, and level of performance was measured before and after studying. The gaming group reported a higher level of interest, challenge, and anxiety of failing after introducing the task. Groups did not differ significantly in their perceived probability of success. The group levels of interest were the same after a one-hour learning phase. When learning, cognitive load increased after the initial phase in the gaming group and then stayed on a constant level, whereas the opposite pattern was found in the hypertext group. No differences were found in load ratings after learning between the two groups. Both groups improved their knowledge after learning, but the gain was larger for the hypertext group. Results point to gaming and English expertise as two mediating factors for learning success with educational games. We suggest that gaming expertise and English comprehension ability reduce cognitive load and thus enable learners to focus their resources on meaningful learning.